Efficacy and safety of Intranasal Ketamine and Midazolam for sedation of young pediatric patients; a double-blind, randomized clinical trial - Hossein Khoshrang; Cyrus Emir Alavi; Siamak Rimaz; Ali Mirmansouri; Farnoush Farzi; Gelareh Biazar; Zahra Atrkarroushan; Nazanin Sabet Khadem (Babol University of Medical Sciences, 2021)
Background: Pediatric patients feel significant fear and anxiety when undergoing surgeries. The ideal drug and its administration route have not been found yet. The aim of this study was to compare the efficacy and safety of intranasal (IN) ketamine and midazolam as premedication in children. Methods: We studied 71 eligible pediatric patients undergoing elective urologic surgeries, aged 2 to 6 years. The degree of sedation and separation scores was compared between the two groups. Additionally, hemodynamic parameters, before premedication, after induction of anesthesia, and during surgery were documented and compared between two groups. Postoperatively, any side effect was recorded as well. Results: Finally, the data from 71 children were analyzed.  Recovery time was significantly longer in group K (ketamine) compared to group M (midazolam); 27.86±4.42 vs 38.19± 6.67 minutes respectively (P=0.01). No significant difference was observed in terms of sedation score between two groups of K & M; 3.29±0.78 vs 3 ±0.71 respectively (P=0.17), and not regarding separation score; 2.51±0.61 & 2.31 ±0.52 respectively (P=0.01). Vital signs were kept within the physiological limits in both groups with no marked fluctuations. Conclusion: To produce sedation in young children, both midazolam and ketamine were effective and safe by IN route.